"No Pope Here": Britain, the Vatican, the IRA, and the Papal Visit to Ireland, September 1979. Issue 3 (September 2021) - Doherty, Martin
Abstract: It is often assumed, particularly by outsiders, that the conflict in Northern Ireland—known euphemistically as "the Troubles"—in which some 3, 600 people lost their lives, was an atavistic throwback to Europe's religious wars of earlier centuries. In 1979, by which time some 2, 000 people had already been killed in the Troubles, Pope John Paul II proposed to pay a visit to Ireland and perhaps to cross the border into Ulster's sectarian cockpit. The idea provoked outrage from some Ulster Protestants and high anxiety for the British, concerned that the Pope might inadvertently inflame the situation or embarrass the British by raising difficult issues. But there were hopes, too, that an unequivocal condemnation of violence by the head of the Catholic Church might help to bring the conflict to an end. This article, based on extensive research in diplomatic archives, reveals deep divisions within the Catholic Church on the Irish question and points to the power and limitations of the British diplomatic reach into the Vatican. It reveals also, however, the powerlessness of prayer and pleadings in the face of terrorist violence.